Anti-Inflammatory Effect for Atherosclerosis Progression by Sodium-Glucose Cotransporter 2 (SGLT-2) Inhibitor in a Normoglycemic Rabbit Model - Lee, Seul-Gee; Lee, Seung-Jun; Lee, Jung-Jae; Kim, Jung-Sun; Lee, Oh-Hyun; Kim, Choong-Ki; Kim, Darae; Lee, Yong-Ho; Oh, Jaewon; Park, Seil; Jeon, Ok-Hee; Hong, Sung-Jin; et al. (Korean circulation journal, 2020)
We sought to investigate an anti-atherosclerotic and anti-inflammatory effect of sodium-glucose cotransporter-2 (SGLT-2) inhibitors in normoglycemic atherosclerotic rabbit model. Male New Zealand white rabbits (n=26) were fed with a 1% high-cholesterol diet for 7 weeks followed by normal diet for 2 weeks. After balloon catheter injury, the rabbits were administered with the Dapagliflozin (1mg/kg/day) or control-medium for 8 weeks (n=13 for each group). All lesions were assessed with angiography, optical coherence tomography (OCT), and histological assessment. Atheroma burden (38.51±3.16% vs. 21.91±1.22%, p<0.01) and lipid accumulation (18.90±3.63% vs. 10.20±2.03%, p=0.047) was significantly decreased by SGLT-2 inhibitor treatment. The SGLT-2 inhibitor group showed lower macrophage infiltration (20.23±1.89% vs. 12.72±1.95%, p=0.01) as well as tumor necrosis factor (TNF)-α expression (31.17±4.40% vs. 19.47±2.10%, p=0.025). Relative area of inducible nitric oxide synthase⁺ macrophages was tended to be lower in the SGLT-2 inhibitor-treated group (1.00±0.16% vs. 0.71±0.10%, p=0.13), while relative proportion of Arg1⁺ macrophage was markedly increased (1.00±0.27% vs. 2.43±0.64%, p=0.04). As a result, progression of atherosclerosis was markedly attenuated in SGLT-2 inhibitor treated group (OCT area stenosis, 32.13±1.20% vs. 22.77±0.88%, p<0.01). Mechanistically, SGLT-2 treatment mitigated the inflammatory responses in macrophage. Especially, Toll-like receptor 4/nuclear factor-kappa B signaling pathway, and their downstream effectors such as interleukin-6 and TNF-α were markedly suppressed by SGLT-2 inhibitor treatment. These results together suggest that SGLT-2 inhibitor exerts an anti-atherosclerotic effect through favorable modulation of inflammatory response as well as macrophage characteristics in non-diabetic situation.